PENERAPAN SIMULASI SOSIAL DALAM MENINGKATKAN SIKAP TOLERANSI DAN KERJA SAMA SISWA SEKOLAH DASAR - Nursanda (ADISAM PUBLISHER, 2026)
This study aims to examine how the implementation of social simulation can improve tolerance and cooperation among elementary school students. The research was motivated by the observation that some students still struggle to respect differing opinions and to collaborate effectively during group activities. Tolerance and cooperation are essential values that should be developed from the early stages of education as part of character building. The study employed a quantitative approach using a Classroom Action Research (CAR) design conducted in two cycles. Each cycle included planning, action, observation, and reflection stages. The participants were fifth-grade elementary school students. Data were collected through observation, attitude questionnaires, and documentation of classroom activities. the findings reveal an improvement in students’ tolerance and cooperation after the implementation of social simulation activities. Students became more engaged in discussions, more accepting of their peers’ perspectives, and more responsible in completing group tasks. Through simulation activities, students experienced social situations more directly, which helped them better understand and practice tolerance and cooperation. Therefore, social simulation can be considered an effective instructional strategy to support character development in elementary schools.